Pathological demography of native patients in a nephrology center in China - 陈惠萍 唐政 曾彩虹 胡伟新 王庆文 俞雨生 姚小丹 王建平 朱茂艳 周虹 刘红 刘志红 黎磊石 (Chinese medical journal, 2003)
Objective To analysis the pathological demography in Chinese patients undergoing renal biopsy from our niphrology center.Methods Between January 1979 and October 2000 in Jinling Hospital, Nanjing, China, 10 002 attempts of percutaneous renal were performed in patients with renal disease from 33 provinces of China. The pathological classifications were made according to the WHO criteria of 1982 for renal pathology or the modified WHO criteria of 1995 by a panel of pathologists and nephrologists during routine clinical-pathological rounds. The pathological demography between those specimens collected from 1979 - 1989 and those from 1990 - 1999 was compared.Results The mean age of the 10 002 subjects undergoing renal biopsy was 31.4 ± 13. 0 years( ranging from 1 to 78 years), with a male to female ratio of 1.3 : 1 ; for the 592 renal transplant recipients, the mean age was 37. 5 ±9. 1 years (ranging from 16 to 66 years), with a male to female ratio of 2. 36: 1. Primary glomerular diseases (PGD) accounted for 71% of the total patients undergoing renal biopsies, secondary glomerular nephritis (SGN) 23%, tubular-interstitial diseases 3.2%, unclassified renal diseases 1.3%, hereditary and congenital renal diseases 1.0%, end stage renal diseases 0. 96%, and recently realized or rare renal diseases 0. 15%. IgA nephropathy (IgAN)was the most frequent pathological pattern (40%) of PGD, followed by mesangial proliferative lesion (MsPL) (30%), membranous nephropathy (MN) (10%), and focal segmental glomerulosclerosis (FSGS) (6%). Lupus nephritis (LN) was the most pathology common seen (74%) in SGN. During the 22 years of the study pedod, there was a steady increase in patients with SGN discovered during pathological evaluation of renal disorders. A rise in prevalence was found in IgA nephropathy, MN( both P < 0. 001 ), crescentic glomerulonephritis ( P < 0. 0001 ), anti-GBM disease, and hemolytic-uremic syndrome/thrombotic thrombocytopenic purpura related renal damages ( both P < 0. 001 ).There was a decrease in endocapillary proliferative glomerulonephritis (P < 0. 001 ) and IgM nephropathy (IgMN) ( P < 0. 01 ) from 1990 - 1999 as compared to 1979 - 1989. Infrequent renal pathological entities were also diagnosed in this group, including Niemann Pick disease, Fabry' s disease, POEMS syndrome, and lipoprotein glomerulonephropathy.Conclusions This is the largest series of renal biopsy data in China, and therefore may reflect the demographic picture of renal diseases in this country. Changes in prevalence of renal pathological entities were reflected in this group of patients over the last 22 years. In primary glomerular diseases,IgA nephropathy is still the most frequently observed pathological pattern. In SGN, LN appeared the most often. Increased prevalence was found in anti-GBM nephritis and HUS/TTP.